Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
Photo of Pitch Lake in Trinidad. Workers are visible and digging pitch. Postcard No.12.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; [1910]; Forests and forestry--Trinidad and Tobago; Employees--Trinidad and Tobago; Work; Blue collar workers--Trinidad and Tobago; Men--Trinidad and Tobago; Working class--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Manual work--Trinidad and Tobago; Pitch Lake, The (La Brea)